Symposium 4: Networked Learning and Interculturality: Perspectives on Working in Intercultural Contexts: Symposium Introduction - McConnell, David (Proceedings of the International Conference on Networked Learning, 2008)
Increasingly, higher education is becoming the setting for intercultural education, where those involved are often from different cultures and may therefore hold different beliefs, values and expectations about the nature of learning, teaching, scholarship and research. Higher education institutions in many "westernised" countries now recruit large numbers of students from overseas: these students are a significant source of funds for these universities. Accommodating international students into 'local' higher education settings is therefore a challenge to many HE teachers. Requiring overseas students to merely 'integrate' into the local HE culture is unlikely to be the answer. Moving to forms of interculturally sensitive learning and teaching practices is more likely to prove acceptable to the overseas students as well as being practically and perhaps also ethically acceptable to the teachers and universities involved. Teachers and students alike have to develop new forms of cultural communication. This is the focus of this symposium. This symposium will look at Networked Learning in the emerging and important context of intercultural learning where teachers and students from different cultural settings are working in geographically dispersed contexts. The six papers making up this symposium consider the nature of culture and interculturality from a variety of different but inter-related perspectives: Banks, McConnell and Bowskill consider a recent online intercultural course where students and tutors came from the UK and China, and where the course design explicitly tried to provide an integrated and purposeful intercultural experience for all involved (see http://csalt.lancs.ac.uk/echina). They consider the possibility of teachers and students developing what some call 'intercultural' competence in these educational settings, and ask the question is that possible? Bowskill, McConnell and Banks examine the same course but from the perspective of tutor development and integration. Against a literature background of little if any practical and theoretical understanding of how to develop online course tutors for participating in a virtual, intercultural course they suggest that a reflective 'space' in which the online tutors can communicate and share practical and theoretical experiences is a good way forward. McConnell, Bowskill and Banks (again in the same context) consider higher education teachers conceptions of e-learning in the UK and in China. Their interest here stems from their experience of working over several years in the Sino-UK eChina e-learning programme during which they developed Masters level online courses. During this period they came to realise that intercultural exchanges in course development between the UK and China were paramount, and that it was necessary for all those involved to understand each other's conceptions of learning and teaching in order to ensure high levels of authentic course development. Reynolds considers the case of international students, the application of participative methods in teaching and the possibility of greater cultural differences at play. The paper examines the experience of teaching multinational students in cooperative learning contexts, and considers the consequences of different research approaches in interpreting the meaning of these experiences. Trehan's paper focuses on the adoption of a critical psychodynamic approach to our understanding of collaborative assessment processes in networked learning which have the aim of supporting diversity and difference. Her aim is to illuminate the dynamics of these processes, and by doing so show how little these processes do in reality support diversity and difference. In Zhang's paper we return to the context of the Sino-UK e-learning programme. Here, the experiences of Chinese students taking the course are examined. Despite a prior belief that the technology of the virtual learning environment and the need to communicate in English might impede Chinese students' capacity to take part in the course and learn, Zhang shows that in fact this was not the case. She says that he major factors impeding these students ability to participate in the course was their wish to save "face" in their online communications, and their belief in the authority of the text and the teacher. The implications of this for the design and implementation of intercultural online courses is considered by the author.